2002
DOI: 10.1210/jcem.87.3.8343
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic Acid Decarboxylase Antibody Positivity Is Associated with an Impaired Insulin Response to Glucose and Arginine in Nondiabetic Patients with Autoimmune Thyroiditis

Abstract: To study whether antibodies to glutamic acid decarboxylase (GADab) are associated with subclinical beta-cell damage and impaired insulin secretion, we screened 441 nondiabetic patients with autoimmune thyroiditis (AT) for GADab, and 15 (3.4%) were found positive. Antibodies to IA-2 were found in two GADab+ and one GADab- patients. We matched 11 GADab+ and 13 GADab- AT patients who were euthyroid on thyroxin supplementation, and 13 control subjects for sex, age, and body mass index and measured insulin, C-pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
2
14
1
Order By: Relevance
“…Measurements of GADA and IA-2A are recommended for initial confirmation of the suspected diagnosis of T1DM or for the prediction of T1DM in research settings (26).Our prevalence of either GADA or IA-2A was similar to findings in the previous studies (18,19,(27)(28)(29).While there was a significantly lower frequency and level of either GADA or IA-2A in the AITD patients compared with that in the T1DM patients, the results were still significant higher than in the healthy subjects, thus partly confirmed the findings on GADA of Kawasaki et al (19). Take into consideration the early study from Kawasaki et al(30)which demonstrated that the level of GADA in T1DM with AITD were found to be significantly higher than in patients without AITD, and the recent Chinese study revealing the high level of GADA to be a strong predictor of the development of thyroid autoimmunity in patients with autoimmune diabetes (31), as well as the finding of Lethagen et al (32) that GADA positivity could be a marker of subclinical insulitis in non-diabetic patients with autoimmune thyroiditis, and the strong connection which Brorsson et al (9) figured out that GADA is related to both increasing age and human leukocyte antigen (HLA) DQ2/DR3, we conclude that the presence of GADA may be a marker of concurrent or successive thyroid autoimmunity and islet autoimmunity. Piliaet al (18)observed that IA-2A was significantly prevalent in Sardinian children with autoimmune thyroiditis, which is consistent with our results to some degree, however, their prevalence of GADA showed no significant differences compared with healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…Measurements of GADA and IA-2A are recommended for initial confirmation of the suspected diagnosis of T1DM or for the prediction of T1DM in research settings (26).Our prevalence of either GADA or IA-2A was similar to findings in the previous studies (18,19,(27)(28)(29).While there was a significantly lower frequency and level of either GADA or IA-2A in the AITD patients compared with that in the T1DM patients, the results were still significant higher than in the healthy subjects, thus partly confirmed the findings on GADA of Kawasaki et al (19). Take into consideration the early study from Kawasaki et al(30)which demonstrated that the level of GADA in T1DM with AITD were found to be significantly higher than in patients without AITD, and the recent Chinese study revealing the high level of GADA to be a strong predictor of the development of thyroid autoimmunity in patients with autoimmune diabetes (31), as well as the finding of Lethagen et al (32) that GADA positivity could be a marker of subclinical insulitis in non-diabetic patients with autoimmune thyroiditis, and the strong connection which Brorsson et al (9) figured out that GADA is related to both increasing age and human leukocyte antigen (HLA) DQ2/DR3, we conclude that the presence of GADA may be a marker of concurrent or successive thyroid autoimmunity and islet autoimmunity. Piliaet al (18)observed that IA-2A was significantly prevalent in Sardinian children with autoimmune thyroiditis, which is consistent with our results to some degree, however, their prevalence of GADA showed no significant differences compared with healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…In Swedish patients, GADA was detected in 13% of newly diagnosed GD patients without clinical diabetes mellitus and in 3.4% of HT patients (18,25). In Japanese patients, GADA was found in 6% of GD and 7.9% of HT patients (17) although the time since thyroid disease diagnosis was not reported, and the patients were in different degrees of thyroid function.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that positive GADA HT patients had similar FPG and insulin concentrations than negative GADA subjects; however, when submitted to arginine injection, they showed a decline in the insulin secretory capacity and the glucagon response to arginine (25).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 40/47 patients completed the 5 year study, which included information about adverse events. GADA and IA-2A were determined as previously described [8]. However, after 12 months, only GADA was analysed.…”
Section: Methodsmentioning
confidence: 99%